Pharmacokinetic interactions of almorexant with midazolam and simvastatin, two CYP3A4 model substrates, in healthy male subjects - Hoch, Matthias; Hoever, Petra; Alessi, Federica; Theodor, Rudolf; Dingemanse, Jasper (European journal of clinical pharmacology, 2013)
Purpose Pre-clinical experiments have shown that almorexant, a dual orexin receptor antagonist, is able to inhibit cytochrome P450 3A4 (CYP3A4). Therefore, a study was conducted to investigate the effects of multiple-dose almorexant on the pharmacokinetics of midazolam and simvastatin, two CYP3A4 model substrates. Methods Fourteen healthy male subjects were enrolled in an open-label, randomized, two-way crossover study. Treatment period A consisted of a single oral dose of 2 mg midazolam on day 1 and 40 mg simvastatin on day 3. In treatment period B, subjects received 200 mg almorexant once daily for 9 days together with a single oral dose of midazolam on day 7 and simvastatin on day 9. Results Concomitant administration of midazolam with almorexant at steady-state levels, achieved within 4–5 days, resulted in an increase of 1.2-fold [90 % confidence interval (CI) 1.0–1.4], 1.4-fold (90 % CI 1.2–1.6), and 1.3-fold (90 % CI 1.2–1.4) in the maximum plasma concentration (C max ), area under the concentration–time curve from time 0 to infinity (AUC 0-∞ ), and terminal half-life (t 1/2 ), respectively, of midazolam; the time to peak plasma concentration (t max ) was unchanged. Whereas C max and t max were not influenced by almorexant, the AUC 0-∞ of hydroxy-midazolam increased by 1.2-fold (90 % CI 1.1–1.4) and the t 1/2 by 1.3-fold (90 % CI 1.0–1.5). Concomitant administration of simvastatin with almorexant at steady-state resulted in an increase of 2.7-fold (90 % CI 2.0–3.7) and 3.4-fold (90 % CI 2.6–4.4) in C max and AUC 0-∞ , respectively, for simvastatin; the t 1/2 and t max were unchanged. The C max and AUC 0-∞ of hydroxyacid simvastatin both increased by 2.8-fold, with 90 % CIs of 2.3–3.5 and 2.2–3.5, respectively; the t max increased by 2 h and the t 1/2 was unchanged. The urinary 6-β-hydroxycortisol/cortisol ratio was unaffected by almorexant. Conclusions Our results suggest that the observed interaction was caused by the inhibition of CYP3A4 activity, most probably at the gut level.